2016
DOI: 10.1007/s10162-016-0560-1
|View full text |Cite
|
Sign up to set email alerts
|

Six Degrees of Auditory Spatial Separation

Abstract: The location of a sound is derived computationally from acoustical cues rather than being inherent in the topography of the input signal, as in vision. Since Lord Rayleigh, the descriptions of that representation have swung between Blabeled line^and Bopponent process^models. Employing a simple variant of a twopoint separation judgment using concurrent speech sounds, we found that spatial discrimination thresholds changed nonmonotonically as a function of the overall separation. Rather than increasing with sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 72 publications
(59 reference statements)
3
12
1
Order By: Relevance
“…Both auditory (Mills, 1958; Makous and Middlebrooks, 1990; Charbonneau et al , 2013; Wood and Bizley, 2015; Carlile et al , 2016) and visual localisation acuity declines with eccentricity (Mateeff and Gourevich, 1984; Perrott et al , 1993; Charbonneau et al , 2013). Few studies have attempted to directly compare spatial acuity for auditory and visual stimuli throughout the visual field and focus instead on the spatial capture observed when spatially separated auditory-visual signals are presented (Howard and Templeton, 1966; Bertelson and Radeau, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Both auditory (Mills, 1958; Makous and Middlebrooks, 1990; Charbonneau et al , 2013; Wood and Bizley, 2015; Carlile et al , 2016) and visual localisation acuity declines with eccentricity (Mateeff and Gourevich, 1984; Perrott et al , 1993; Charbonneau et al , 2013). Few studies have attempted to directly compare spatial acuity for auditory and visual stimuli throughout the visual field and focus instead on the spatial capture observed when spatially separated auditory-visual signals are presented (Howard and Templeton, 1966; Bertelson and Radeau, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…This was consistent with the idea that averaging heterogeneous spatial receptive fields leads to loss of information 36,37,48 . Increasing the number of channels past ~20 did not substantially improve population decoding performance, suggesting that there may be an upper limit on spatial resolution for absolute localisation of auditory stimuli in the cortex, as has been suggested in humans 51 .…”
Section: Discussionmentioning
confidence: 75%
“…Previous work has suggested that spatial representations in the auditory cortex may comprise three channels 49,50 , or many channels with 6° widths tiling space 51 . In order to investigate these ideas further, we modified our two-channel decoder to compare decoding performance of neural populations divided into N channels according to spatial tuning observed in response to BBN stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both auditory(Mills, 1958; Makous and Middlebrooks, 1990; Charbonneau et al, 2013; Wood and Bizley, 2015; Carlile et al, 2016) and visual localisation acuity declines with eccentricity (Mateeff and Gourevich, 1984; Perrott et al, 1993; Charbonneau et al, 2013; Carlile et al, 2016). Few previous studies have attempted to directly compare spatial acuity for auditory and visual stimuli throughout the visual field and focus instead on the spatial capture observed when spatially separated auditory-visual signals are presented (Howard and Templeton, 1966; Bertelson and Radeau, 1981).…”
Section: Introductionmentioning
confidence: 99%